An Experimental Study of a Peer-Facilitated Violence Prevention Program for Women in Prison. Issue 17 (September 2022) - Messina, Nena P.; Calhoun, Stacy
The literature has shown a strong correlation between victimization and violence. As the majority of treatment programs for violence and the associated research have been focused on men, it is vital that services are also oriented to the needs of women who perpetrate violence. Beyond Violence ( BV ) was developed to fill the gap in violence prevention programming for justice-involved women with histories of violence victimization and perpetration. This randomized controlled trial reports the results of a peer-facilitated model of the BV program implemented in a women's prison. Women volunteered for the intervention and the study. Participants were randomized to either the 20-session BV condition or to a waitlist control (WC) condition. All 145 participants were asked to complete a preintervention (Time 1) and postintervention (Time 2) survey that included validated measures to assess for depression, anxiety, PTSD, anger/aggression, and emotional dysregulation. Preliminary analyses of the background characteristics and preintervention outcome scores showed no significant differences between the groups at Time 1, indicating that randomization was successful. Separate ANCOVAs were run for 13 outcomes measured using the pretest scores from study participants as the covariate and group assignment as the independent variable. Hypotheses were predominantly supported, and findings showed that the BV participants had significant reductions in the majority of the outcome measures at the postintervention assessment when compared to the WC participants. Future research should continue to explore the advantages of peer-facilitated program models and should incorporate postrelease outcomes to assess change over time.